Predictors to increase safety technology adoption in construction: an exploratory factor analysis for Malaysia - Yap, Jeffrey Boon Hui; Lee, Karen Pei Han; Skitmore, Martin; Lew, Yoke Lian; Lee, Wah Peng; Lester, Danielle (Journal of Civil Engineering and Management, 2023)
Accidents and injuries continue to be major problems in the construction industry despite persistent endeavours over the years to improve health and safety management. Novel approaches using emerging technologies can enhance construction safety performance. Given their limited adoption and lack of empirical evidence in the context of developing countries, this paper examines the predictors influencing the successful adoption of safety technologies in the construction industry. Using a survey questionnaire involving 133 Malaysian construction professionals, the significance of the predictors is prioritised. A factor analysis is used to reduce the predictors involved into a fewer number of dimensions. The most influential predictors are presented. Four underlying dimensions of the surveyed predictors are uncovered, comprising organisational commitment/technology orientation, supporting technological attributes, personal perception/performance expectancy and government support. The rate of technology implementation to improve safety risk mitigation in construction is still limited. By taking cognisance of the critical influential predictors involved, the adoption level of safety technology could be raised. This paper bridges the identified knowledge gap regarding the dimensionality of safety technology adoption predictors in construction, with findings that shed new light on the factors influencing technology adoption in a developing country to stimulate technological innovations to streamline construction safety. First published online 20 December 2022